Elite young soccer players have smaller inter-limb asymmetry and better body composition than non-elite players - Mala, Lucia; Hank, Mikulas; Stastny, Petr; Zahalka, Frantisek; Ford, Kevin; Zmijewski, Piotr; Bujnovsky, David; Petr, Miroslav; Maly, Tomas (Biology of Sport, 2023)
Body composition (BC) and inter-limb anthropometric asymmetries (LA) may influence the physical performance of soccer players. This study aimed to determine differences in BC and LA among soccer across four performance levels. The study involved 110 male soccer players participating in Czech senior teams who were grouped into four different performance levels (i.e. G1: national team, G2: 1st division, G3: 2nd division, G4: 3rd division). The following BC and LA parameters were compared among groups: body height, body mass, absolute fat-free mass, relative fat-free mass (FFMrel), percentage of fat mass (FM), total body water (TBW), intracellular water (ICW), extracellular water (ECW), phase angle, and bilateral muscle mass differences in the upper and lower extremities. Significant differences were observed in BC parameters among all groups (λ = 0.06, F 75,246 = 5.38, p = 0.01, η p 2 = 0.62). High-performance players (i.e. G1, G2) had significantly (p < 0.01) lower FM than lower performance players (i.e. G3, G4). The lowest values of FFMrel, relative TBW, relative ICW and ECW were detected in the lowest-performance players (i.e. G4). Significantly lower bilateral muscle mass differences were detected in G1 players (2.71 ± 1.26%; p < 0.01) compared with G4 players (3.95 ± 1.17%). G1 and G2 players had a higher proportion of muscle mass in the torso (p < 0.01) and upper limbs than G3 and G4 (p < 0.01). Elite and high-performance players have better BC and lower inter-limb anthropometric asymmetries compared with low-performance level players.